Design of a model for implementing leagile manufacturing paradigm in the pump industry. (19th March 2019) - Balakrishnan, K.; Devadasan, S.R.; Murugesh, R.
In this paper, a research about designing a model for implementing leagile manufacturing paradigm in the pump industry is reported. This research was carried out in three phases. During the first phase, theoretical knowledge on leagile manufacturing paradigm was gathered by reviewing the literature. During the second phase, practical knowledge was gathered by designing the infrastructure required for implementing leagile manufacturing paradigm in a traditional pump manufacturing company. During the third phase, the theoretical and practical knowledge gathered during the previous two phases were utilised to design a model for implementing leagile manufacturing paradigm in the pump industry. This model has been named as pumping for leagility (PFL). The working of PFL model is illustrated by narrating a hypothetical case study. PFL can facilitate both researchers and practitioners to implement leagile manufacturing paradigm in pump manufacturing companies in eight steps. These endeavours will enable the pump industry to gain competitive strength.